Exploring palatal and dental shape variation with 3D shape analysis and geometric deep learning. (24th August 2021) - Nauwelaers, Nele; Matthews, Harold; Fan, Yi; Croquet, Balder; Hoskens, Hanne; Mahdi, Soha; El Sergani, Ahmed; Gong, Shunwang; Xu, Tianmin; Bronstein, Michael; Marazita, Mary; Weinberg, Seth; et al.
Abstract: Objectives: Palatal shape contains a lot of information that is of clinical interest. Moreover, palatal shape analysis can be used to guide or evaluate orthodontic treatments. A statistical shape model (SSM) is a tool that, by means of dimensionality reduction, aims at compactly modeling the variance of complex shapes for efficient analysis. In this report, we evaluate several competing approaches to constructing SSMs for the human palate. Setting and Sample Population: This study used a sample comprising digitized 3D maxillary dental casts from 1, 324 individuals. Materials and methods: Principal component analysis (PCA) and autoencoders (AE) are popular approaches to construct SSMs. PCA is a dimension reduction technique that provides a compact description of shapes by uncorrelated variables. AEs are situated in the field of deep learning and provide a non‐linear framework for dimension reduction. This work introduces the singular autoencoder (SAE), a hybrid approach that combines the most important properties of PCA and AEs. We assess the performance of the SAE using standard evaluation tools for SSMs, including accuracy, generalization, and specificity. Results: We found that the SAE obtains equivalent results to PCA and AEs for all evaluation metrics. SAE scores were found to be uncorrelated and provided an optimally compact representation of the shapes. Conclusion: We conclude that the SAE is a promising tool for 3D palatal shape analysis, which effectively combines the power of PCA with the flexibility of deep learning. This opens future AI driven applications of shape analysis in orthodontics and other related clinical disciplines.